Handling of Consumer Defaults at PT Adira Finance from the Perspective of Islamic Economics Ethics - Muhammad Kusnady Tabsir; Arfin Hamid; Irwan Misbach (PT FORMOSA CENDEKIA GLOBAL, 2023)
Defaults in motor vehicle loan agreements by consumers occur because of the consumptive nature of customer is not directly proportional to their income. In addition there is a bad faith from some consumer not to carry out their obligation as they should. The purpose of this study was to analyze the handling of defaults on motor vehicle agreements at PT Adira finance. This study used qualitative research method with field research. The result show that PT Adira Finance in dealing with the consumers default in motor vehicle loan agreements from the perspective of the Islamic business ethics has implemented several basic principles of business ethics in Islamic economics especially monotheism, free will, responsibility and truth. While the principle of balance and justice. PT. Adira Finance has not fully applied Islamic economic ethics, especially in term of writing of consumer debt that are eligible for assistance because they meet certain conditions such as going bankrupt